Fonološke baze suškega govora – 120 let po izidu Macedonische Studien (1896) Vatroslava Oblaka - Nikolovski, Gjoko (Slavia Centralis, 2020)
THE PHONOLOGICAL BASE OF THE SUHO DIALECT – 120 YEARS AFTER THE PUBLICATION OF VATROSLAV OBLAK’S MACEDONISCHE STUDIEN (1896) The article deals with the phonological base of the Suho dialect, which belongs to the Macedonian south-east dialect group and Serres-Lagadin subgroup of dialects, which today are located in the northern part of Greece, which was until 1912 part of the territory of ethnic Macedonians. The Slovenian philologist Vatroslav Oblak in 1891-1892 studied the dialects north of Thessaloniki and wrote his Macedonische Studien (1896), in which he described the Thessaloniki Suho dialect. The phonological reflexes that he found in the Suho dialect supported his theory of Thessaloniki-based Old Church Slavonic (1895). This article presents the latest state of phonological basis of the Suho dialect some 120 years after the publication of Oblak’s Macedonische studien.